Pelatihan Pembuatan Pupuk Organik Cair Mengkudu di Gampong Kopelma Darussalam, Banda Aceh - Oktarina, Hartati; Chamzurni, Tjut; Jauharlina, Jauharlina; Sriwati, Rina; Pramayudi, Nur (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2023)
The use of synthetic chemical fertilizers to enhance plant growth has become a common practice in the community. However, continuous use of synthetic chemicals can cause damage to the physical, chemical, and biological properties of the soil. Not only that, but synthetic chemical fertilizers also leave residues on agricultural products that can disrupt human health. Therefore, we conducted community service activities aimed at providing knowledge about the dangers of synthetic chemicals and training in the making of liquid organic fertilizer (LOF) using noni fruit as an environmentally friendly alternative fertilizer material. LOF-making training was given to the Family Welfare Development Group (PKK) in Gampong Kopelma Darussalam, Banda Aceh. The activity began with the delivery of material on the dangers of synthetic chemicals to the environment, followed by a discussion. It was then followed by a practical session on making LOF using noni fruit. From this activity, the PKK group in Gampong Kopelma Darussalam, Banda Aceh, gained knowledge about the dangers of synthetic chemicals and the skills to make LOF that can be used as a substitute for the synthetic chemical fertilizers that they usually use. Furthermore, these skills can also be a source of additional income for local residents.